P17 Clinical features and prognostic factors in patients with head and neck cancer – Results from a multicentric study. Issue 5 (May 2015) - Cadoni, G.; Boccia, S.; Leoncini, E.; Petrelli, L.; Vukovic, V.; Pastorino, R.; Arzani, D.; Bosetti, C.; Canova, C.; Garavello, W.; La Vecchia, C.; Maule, M.; et al.
<x xml:space="preserve">Abstract</x> Background The purpose of this study is to evaluate whether demographics, lifestyle habits, clinical data and alcohol dehydrogenase rs1229984 and rs1573496 associated with first primary head and neck (HNC) are associated with overall survival, recurrence, and second primary cancer (SPC). Methods We conducted a follow-up study in five centres including 801 cases. Hazard Ratios (HRs) and 95% confidence intervals (CIs) were estimated for overall survival, recurrence and SPC. Results Five-years overall survival was 62% for HNC cases, 55% for oral cavity, 53% for oropharynx, 41% for hypopharynx, and 71% for larynx. Predictors of survival were older ages (HR = 1.18 for 5 years increase; CI: 1.09–1.29), higher tumour stage (HR = 3.70; CI: 2.44–5.60), and high alcohol consumption (HR = 3.49; CI: 1.09–11.13). A combined therapy (HR = 3.05; CI: 1.22–7.66), and smoking (HR = 2.35; CI: 1.09–5.04), were associated with a worst prognosis for oral cavity cancer. The only predictor was higher tumour stage (HR = 2.25; CI:1.26–4.03) for recurrence, and duration of smoking (HR = 1.91; CI: 1.00–3.68) for SPC. Conclusions The survival expectation differs among HNC sites. Increasing age and stage, and high alcohol consumption were unfavourable predictors of HNC survival overall, while smoking status was a negative prognostic factor for oral cavity cancer. Duration of tobacco consumption before the first primary tumour was a risk factor for SPC.